(3bUI GdYHGS Hf MeRI eY Pi Gdfhf GdeUQis - (3GdHjgbj , CHh HcQ CMeO Hf GdMSjf Hf Ydj GdHjgbj GdNQGSGfj GdTGaYj, GdHjgbj,J (B458 (3g` s
(3ChdgG (B:s
(3bGd CNHQfG dGTjN CHh HcQ CMeO Hf GdMSjf GdHjgbi bGd SeYJ CHGHcQ eMeO Hf YHO Gddg GHf jhSa GHf HfJ GdYHGS Hf MeRI ZjQ eQg jbhd ONdJ Ydi Pi Gdfhf GdeUQi QMeg Gddg JYGdi hYfOg faQ ef GdeQjOjf s
(3BNQgG (B:s
(3bGd SeYJ eGdckG jbhd bGd GHf GdeSjH Ef cfJ dCSjQ GdCjGe hGddjGdi ai WdH GdMOjK GdhGMO BNQ GdLRA hGdMeO ddg QH GdYGdejf hUdi Gddg Ydi SjOfG eMeO GdfHi GdCei hBdg hUMHg hSde JSdjekG cKjQkG Edi jhe GdOjf s
(3HgG fXGe GdJYbjHIs
(3HBNQgG bUjOI ai NJe GdHNGQis
(3JHUQI GdYfhGf (B:s
(3QhGjI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B116 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B206s
Keywords: (3GdJUha hGdBOGH GdTQYjIs